Mangrove Rehabilitation and Restoration as Experimental Adaptive Management - Ellison, Aaron M.; Felson, Alexander J.; Friess, Daniel A. (Frontiers in Marine Science, 2020)
Rehabilitated and restored mangrove ecosystems have important ecological, economic, and social values for coastal communities. Although a sine qua non of successful mangrove rehabilitation or restoration projects is accurate attention to local hydrology and basic biology of mangrove trees and their associated fauna, their long-term success depends on far more axes, each with their own challenges. Rehabilitation projects: are planned, designed, executed, and managed by people with diverse backgrounds and different scientific and socio-political agendas; need to be responsive to these multiple stakeholders and agents who hold different values; are often influenced by laws and treaties spanning local to international scales; and must be able to adapt and evolve both geomorphologically and socioeconomically over decades-to-centuries in the context of a rapidly changing climate. We view these challenges as opportunities for innovative approaches to rehabilitation and restoration that engage new and larger constituencies. Restored mangrove ecosystems can be deliberately designed and engineered to provide valuable ecosystem services, be adaptable to climatic changes, and to develop platforms for educating nonspecialists about both the successes and failures of restored mangrove ecosystems. When mangrove rehabilitation or restoration projects are developed as experiments, then can be used as case-studies and more general models to inform policy- and decision-makers and guide future restoration efforts. Achieving this vision will require new investment and dedication to research and adaptive management practices. These ideas are illustrated with examples from mangrove restoration and rehabilitation projects in the Indo-West Pacific and Caribbean regions, the two hotspots of mangrove biodiversity and its ongoing loss and degradation.